Exploring the psychopathological profile of fibromyalgia: insights from the personality assessment inventory and its association with disease impact - Doreste, Andrea; Pujol, Jesus; Penelo, Eva; Pérez, Víctor; Blanco-Hinojo, Laura; Martínez-Vilavella, Gerard; Pardina-Torner, Helena; Ojeda, Fabiola; Monfort, Jordi; Deus, Joan (Frontiers in Psychology, 2024)
Background. Fibromyalgia (FM) is a complex rheumatic disorder characterized by chronic nociplastic pain and central sensitization. Psychopathological conditions can influence FM symptoms, which worsen their condition. However, not all patients with FM have psychopathological disorders, indicating a heterogeneous population. Objective. To investigate the psychopathological profile and personality disorders in patients with FM and its relationship impact on this disease. Methods. An observational and cross-sectional comparative study was conducted with a sample of 90 women, mean age 48.7 years (SD=8.12), from Hospital del Mar, Barcelona. The Personality Assessment Inventory (PAI) and the Fibromyalgia Impact Questionnaire (FIQ) were used for assessment. Results. FM patients predominantly exhibited psychopathological profiles resembling affective disorders (37.7%) and Cluster C personality disorders (58.8%). The severity of FM's impact was related to affective disorder symptoms, hypervigilance, derealization, somatization, and Cluster B personality disorder (emotional instability). Different rheumatic symptoms correlated with specific psychopathological patterns. Increased somatic symptoms on the FIQ were related to an unstable and dependent personality, while heightened emotional symptoms on the FIQ were associated with avoidance, borderline traits, and passive-aggressive reactions. Conclusions. Recognizing psychopathological aspects is crucial for managing FM. The PAI is a valuable tool for establishing its psychopathological multidimensional profile, which predominantly shows an affective spectrum conditions and comorbid Cluster C personality disorder, exacerbating the disease's impact.